Action publique, gentrification et compromis sociaux de production urbaine : une comparaison de deux anciens quartiers industriels au Havre et à Leipzig - Antonin Girardin (Métropoles)
This article aims to examine the link between political strategies for transforming two former industrial districts—Saint-Nicolas in Le Havre (France) and Plagwitz in Leipzig (Germany)—and the material and social forms of the gentrification process. Marked by different historical modalities of interventions by public authorities and a dissimilarity of actors involved in urban transformations, the two cities have implemented, since the beginning of the 2000s, reconversion projects of their former industrial districts leveraging strategies that seem at first opposed: a revanchist development strategy planned by public authorities in connection with private promoters in Saint-Nicolas, against a series of more opportunistic redevelopments based on a strategy to mobilise local populations following more ‘social-democratic’ political modalities in Plagwitz. However, these apparent oppositions, which are questioned here, are two sides of the same coin because both strategies have led to residential intensification and the appropriation of former working-class spaces by well-to-do populations, which result in a common observation: the elitist and unequal transformation of former industrial districts.